Photonuclear reactions on p-shell nuclei at intermediate energies - Khodyachikh, A.F. (Вопросы атомной науки и техники, 2003)
Absolute total and differential cross sections for (g,р)-, (g,n)- and (g,pn)- reactions on the ¹²С, ¹⁴N and ¹⁶О nuclei have been measured using a diffusion chamber placed in a magnetic field and irradiated by a beam of bremsstrahlung photons with an end-point energy of 150 MeV. The applicability of photoabsorption model on a correlated proton-neutron pair was proved. It is concluded that models with essential contribution of meson exchange currents provide a qualitative description of energy dependence of total and differential cross sections at energies above 50 MeV.